Effect of 9.3 μm CO2 and 2.94 μm Er:YAG Laser vs. Bur Preparations on Marginal Adaptation in Enamel and Dentin of Mixed Class V Cavities Restored With Different Restorative Systems - Anton y Otero, Clara Isabel; Di Bella, Enrico; Krejci, Ivo; Bortolotto, Tissiana (Frontiers in Dental Medicine, 2021)
This study aimed to compare marginal adaptation in enamel and dentin before and after aging of laser vs. bur-prepared mixed class V cavities restored by different restorative systems. Seventy two caries-free human molars were distributed to nine experimental groups; cavities were prepared using two different lasers: a handpiece -integrated 2.94 μm Er:YAG laser at 4.5 W, 300 mJ, and 0.75 W, 50 mJ with 15 Hz (LiteTouch, Light Instruments, Israel) and a novel CO2 laser at 12.95 W, 19.3 mJ, and 4.1 W, 6.11 mJ with 671 Hz (Solea 9.3 μm, Convergent Dental, USA). Cavities prepared with conventional diamond burs (Intensiv, Switzerland) in a red contra angle at high speed under maximal water cooling served as control. Cavities were prepared under simulation of dentinal fluid and restored using three different self-etching universal adhesives in combination with three nanohybrid composites, applied in two layers: Scotchbond Universal with Filtek Supreme XTE (3M, USA), G-Premio BOND with Essentia Universal (GC, Japan), and OptiBond Universal with Harmonize Universal (Kerr, USA). After restorations' polishing and simultaneous thermal (5–50°C, 2 min each) and mechanical loading (max. 49 N; 200,000 cycles), replicas of restoration margins were examined under SEM at × 200 magnification. Percentages of continuous margins (CMs) were quantified before and after the fatigue test and statistically compared (two-way ANOVA with Fisher's least significant difference [LSD] post hoc test). Significant differences were found in almost all groups between the results before and after the fatigue test, as well as between the different preparation tools and restorative materials (p < 0.05). Traditional bur preparations are confirmed as gold standard in enamel and dentin, as all three tested restorative systems provide results of marginal adaptation of more than 80% CM after loading. Er:YAG laser preparations can be equally effective in combination with SBU/Filtek Supreme XTE. CO2 laser ablation could not provide convincing results with the tested self-etching restorative systems. Marginal adaptation has been highly dependent on the substrate and showed impaired adhesion, especially in enamel. Scotchbond Universal/Filtek Supreme XTE showed the highest and most stable values of CM. The other two restorative systems were highly dependent on the preparation device of the substrate.